The ethnic plots of bioethics - Sedova, Natalia Nikolaevna (Array, 2018)
Bioethics of the ethnos has meanings that reflect the history and culture of a particular people. At the same time, the ethnos in its existence realizes the general bioethical principles and norms that integrate into ethnic bioethics. The ratio of these modifications of bioethics can ensure the self-preserving behavior of the ethnos and help maintain the genetic diversity of mankind. The assessment and standards in modern bioethics cannot be exactly the same for all countries and peoples; they must match the ethnic age of this particular ethnic group. Thus, scientifically-invariant biomedical ethics always functionally acts as a cultural reflection of the national model of medicine. On the other hand, the normative bioethical regulation allows adapting the National standards of medicine as a cultural complex to international requirements. The article shows the options for the ethical support of various ethnic parameters in medicine.